Determinan Penghindaran Pajak: Bukti di Indonesia - Agrianata Dika; Theresia Woro Damayanti (Wahana: Jurnal Ekonomi, Manajemen dan Akuntansi, 2023)
The biggest source of state income comes from taxes. But until now many citizens still consider tax as a burden. The company or entity still considers tax as an expense that will reduce the company’s net profit. The purpose of the study was to analyze the effect of firm size, profitability, leverage on tax avoidance. The population of this research is the entire manufacturing company registered in Indonesia stock exchange (BEI) 2015-2019 during the period. Sample selection using non-probability sampling method with purposive sampling technique. The results of the analysis show that firm size and leverage have no effect on tax avoidance while profitability has a negative effect on tax avoidance. This shows that the higher the profitability, the lower the tax avoidance.